Reduced probability of improving viro‐immunological state in subjects with vertical transmission of HIV reaching adult age: A multicenter retrospective cohort study. Issue 2 (9th February 2023) - Pennati, Francesca; Calza, Stefano; Di Biagio, Antonio; Mussini, Cristina; Rusconi, Stefano; Bonora, Stefano; Borghetti, Alberto; Quiros‐Roldan, Eugenia; Sarteschi, Giovanni; Menozzi, Marianna; Ferrara, Micol; Celotti, Anna; et al.
Abstract: Introduction: Young adults with vertical transmission (VT) of human immunodeficiency virus (HIV) represent a fragile population. This study evaluates factors associated with viro‐immunological outcome of these patients. Methods: We performed a multicenter study including HIV‐infected subjects with VT ≥ 18 years old from six Italian clinics. Subjects were observed from birth to death, lost to follow‐up, or last visit until December 31, 2019. Condition of "optimal viro‐immunological status" (OS) was defined as the simultaneous presence of HIV ribonucleic acid (RNA) < 50 copies/mL, CD4+ > 500 cells/mm 3, and CD4+/CD8+ ratio ≥ 1. Results: A total of 126 subjects were enrolled. At 18 years of age, 52/126 (44.4%) had HIV‐RNA > 50 copies/mL, 47/126 (38.2%) had CD4+ < 500/mm 3, and 78/126 (67.2%) had CD4+/CD8+ < 1; 28 subjects (23.7%) presented in the condition of OS. Having a CD4+/CD8+ ratio ≥ 1 at 18 years of age was related with an increased probability of shift from suboptimal viro‐immunological status (SOS) to OS (HR: 7.7, 95% confidence interval [CI]: 4.23–14.04), and a reduced risk of shift from the OS to the SOS (HR: 0.49, 95% CI: 0.26–0.92). Acquired immunodeficiency syndrome (AIDS) diagnosis significantly reduced the probability of shift from a viro‐immunological SOS to OS (HR: 0.09, 95% CI: 0.03–0.30). Subjects who had not achieved an OS at 18 years of age had an increased risk of discontinuation of combination antiretroviral therapy (cART, p  = .019). Conclusions: Only a small proportion of subjects with VT of HIV reached the adult age with "OS". Transition to the adult care with a compromised viro‐immunological condition represents a negative driver for future optimal infection control, with a higher risk of discontinuation of cART and a reduced probability to improve the immunological status later in the years. Abstract :